Sensory Acceptability of Buffalo Meat and Beef in Young Consumers - Rodríguez-Florentino, René; de la Cruz-Cruz, Luis A.; Roldán-Santiago, Patricia; Larrondo, Cristian (Journal of Buffalo Science, 2025)
Background: The aim of this study was to evaluate the sensory acceptability of buffalo meat compared to beef, as well as to evaluate the perception of buffalo meat. Method: The study was conducted with young meat consumers, who responded to a questionnaire with four sections: 1) sociodemographic aspects, 2) consumer preferences, 3) hedonic acceptability, and 4) perception of buffalo meat consumption. Three 2.5 cm thick steaks (Longissimus thoracis et lumborum) were compared: 1) select beef (slight marbling); 2) select buffalo meat (slight marbling); 3) prime beef (abundant marbling). The samples were evaluated by 76 young meat consumers (non-trained panelists). A seven-point hedonic scale was used to assess appearance, odor, flavor, tenderness, juiciness, and overall acceptability. Results: The results indicated that prime beef presented a better appearance (P=0.0042) and tenderness (P<0.0001) compared to select buffalo and select beef, respectively. Similarly, a higher score was observed in juiciness for prime beef (5.52±0.19 points), but a better score for buffalo meat compared to beef select was identified (4.52±0.18 points vs. 3.86±0.19 points, respectively; P<0.001). Most of the panelists indicated that prior to the study, they had not consumed buffalo meat (89.00%/n=68). However, they noted that buffalo meat was like select beef (71.00%/n=54). The panelist highlighted various reasons why buffalo meat is not commonly consumed, such as there is no information on the buffalo meat (93.42%/n=71), limited availability of buffalo meat products (60.52%/n =46), and unavailability at supermarkets (73.69%/n=56). Conclusion: Buffalo meat can be a good option for young consumers. However, more information about buffalo meat characteristics (chemical, nutritional, sensory properties, and technological quality) and improved marketing channels that ensure the availability of buffalo products are important.